Hybrid nanocomposites containing carboxymethylcellulose and silver nanoparticles - De Moura, Márcia R. [UNESP]; Aouada, Fauze A. [UNESP]; Mattoso, Luiz H.C.; Zucolotto, Valtencir (American Scientific Publishers, 2013)
Silver nanoparticles have high temperature stability and low volatility, and at the nanoscale are known to be an effective antifungal and antimicrobial agent. The present investigation involves the synthesis of silver nanoparticle/carboxymethylcellulose nanocomposites. The nanoparticles synthesised in this study had sizes in the range of 100 and 40 nm. The nanocomposites formed by a combination of metallic nanoparticles and carboxymethylcellulose were characterised by contact angle measurements, solubility tests, thermal and mechanical analyses, and morphological images. Improvements in the hydrophobic properties were observed with inclusion of the nanoparticles in the nanocomposites, with the best results occurring after the addition of 40 nm nanoparticles in a carboxymethylcellulose matrix. The silver nanoparticles tend to occupy the empty spaces in the pores of the carboxymethylcellulose matrix, inducing the collapse of these pores and thereby improving the tensile and barrier properties of the film. Copyright © 2013 American Scientific Publishers All rights reserved.
Keywords: Carboxymethylcellulose films; Mechanical analyses; Silver nanoparticles; Carboxy methylcellulose; High temperature stability; Hybrid nanocomposites; Hydrophobic properties; Mechanical analysis; Metallic nanoparticles; Thermal and mechanical analysis; Contact angle; Nanocomposites; Nanoparticles; Silver